Pelatihan Lesson Study untuk Meningkatkan Kemampuan Guru dalam Merancang Pembelajaran Efektif - Fine Eirene Siahaan; Sanggam Siahaan; Siska Anggita Situmeang; Basar Lolo Siahaan; Novra Melisa P. Hutabarat (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Lesson study training helps teachers improve their professional competencies, including pedagogical and social skills. Through collaboration and reflection, teachers can learn from each other's experiences, which in turn improves their teaching skills. This community service method uses a training and mentoring approach. This service aims to socialize and develop teachers' skills in designing effective learning through lesson study. The conclusions of the service conducted by the team at SD Negeri 11 Siparmahan are as follows: This socialization succeeded in increasing teachers' understanding of the importance of lesson study as a tool to improve teaching practices. Teachers are now more aware that collaboration and reflection are the keys to achieving quality learning; Through collaborative lesson planning and implementation activities, teachers have developed skills in designing better lesson plans that meet students' needs; This activity has also created a collaborative culture among teachers where they support each other and share experiences. This is important for building a sustainable learning community in the school environment; The reflection process after the implementation of the lesson study allows teachers to evaluate the effectiveness of the teaching strategies used and to find solutions for future improvements; The improved ability of teachers to design effective lessons is expected to have a positive impact on student learning outcomes. More interactive and relevant learning will increase student motivation and involvement in the learning process.